Is special treatment of a minor offender against the best interests of the minor victim? - Elisa Silvennoinen; Tarja Koskela (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The UN Convention on the Rights of the Child, as well as EU regulations, demand that in all actions concerning children, the best interest of the child shall be the primary consideration. This principle also applies to criminal proceedings. Juvenile delinquency is often committed against other juveniles. In Finnish criminal policy and legislation, juvenile offenders are treated more leniently than adults, and the starting point in intervention is education and guidance. In cases where the suspect and the victim are minors, the best interests of the children should be balanced between them. In such cases, the rights of the child should apply equally to both parties. As a result, we found that the best interests of the child in criminal proceedings should be understood as a procedural obligation.